IGF-1 enhances the osteogenic activity of BMP-6 in vitro and in vivo, and together have a stronger osteogenic effect than when IGF-1 is combined with BMP-2 - Rico-Llanos, Gustavo Adolfo; Becerra-Ratia, José; Visser, Rick (My University, 2017)
Bone morphogenetic protein-2 (BMP-2) is widely used in orthopedic surgery and bone tissue engineering because of its strong osteogenic activity. However, BMP-2 treatments have several drawbacks and alternatives are being explored. Since BMP-6 has been demonstrated to be more osteoinductive, its use, either alone or together with other cytokines, might be an interesting option. We have compared the effect of BMP-2, BMP-6, or insulin-like growth factor-1 (IGF-1), either alone or in combination. MC3T3-E1 cells were treated with IGF-1 and/or of BMP-2 or -6 and the expression of osteogenic genes, proliferation and alkaline phosphatase (ALP) activity in vitro were analyzed. The results showed that IGF-1 greatly enhanced the BMP-induced osteogenic differentiation of these cells and that the ALP activity in the cultures was higher when the combination was made with BMP-6 than with BMP-2. Other in vitro experiments showed that the osteogenic effect of these combinations can be modulated controlling the sequential administration of the growth factors. Furthermore, we have tested the osteogenic potential of these treatments in vivo by loading them onto absorbable collagen sponges which were implanted into an ectopic bone formation model in rats. These experiments revealed that only BMP-6 was able to induce bone formation at the used dose and that the addition of IGF-1 contributed to an increase of the mineralization in the implants. Hence, the combination of BMP-6 with IGF-1 might be a better alternative than BMP-2 for orthopedic surgery and bone tissue engineering approaches with potential application through using controlled delivery systems.
Keywords: Ingeniería de tejidos; Bone; Tissue engineering; Bone morphogenetic proteins; Insulin-like growth factor; Collagen